Who needs big banks? The real effects of bank size on outcomes of large US borrowers - Biswas, Swarnava (Sonny); Gómez, Fabiana; Zhai, Wei (Journal of Corporate Finance, 2017)
We examine how bank size affects borrowers, when information asymmetry is not particularly severe. Our sample comprises 20,806 loan facilities granted to 3625 US public firms. After minimizing endogeneity concerns, we find that there is a positive relation between bank size and firm value, after the origination of the loan. Firms that borrow from large banks invest more, grow faster and have higher risk, proxied by earnings volatility. The effects are concentrated in borrowers which are ex-ante (pre-loan) safer (low leverage or high Z-score) and muted, but not negative, in riskier firms. We highlight the bright side of large banks.